Peran Guru PAI dalam Menanamkan Ketakwaan dan Moral Pelajar pada Era Society di SDN 2 Tamanasri - Putra, Beni Angga Permana; Sayekti, Sanjaka (Lembaga Yasin AlSys, 2025)
The Society 5.0 era has instigated profound transformations in various sectors, particularly in education, necessitating a strategic intervention from Islamic Education (PAI) teachers in molding students' character and instilling values of piety and morality. This study aims to investigate the role of PAI teachers in confronting the challenges posed by the Society 5.0 era and to delineate the factors that both support and inhibit the cultivation of values. Employing a descriptive qualitative approach, the research reveals that PAI teachers function as educators, mentors, role models, and motivators, playing a crucial role in promoting noble character and piety among students. Key supporting factors identified include the effective utilization of digital technology, robust backing from the school and family environments, and teachers’ proficiency in merging religious values with contemporary developments. Conversely, inhibiting factors encompass the detrimental impacts of social media, insufficient parental oversight, and the restricted time allocated for religious education within school curricula. Consequently, fostering synergy among teachers, schools, families, and the broader community is imperative to enhance moral and spiritual education in the face of technological evolution. This research offers vital implications for the advancement of more effective strategies in Islamic Religious Education (PAI) within the digital age and emphasizes the importance of collaborative efforts among teachers, parents, and the community in nurturing students' noble character.